(untitled) (Research, Society and Development, 2021)
The demand for water has become growing due to population increase and agro-industrial development. The increased by demand generates further exploration of the underground watersheds, since many superficial sources are unable to meet the demand required. At work we evaluated the destination of use of groundwater, of the wells drilled in the municipality of São José do Rio Preto, in the 1950, 1960, 1970, 1980, 1990, 2000 and 2010. Was used info flow, depth, date and type of water use of 801 wells. Data were collected in the DAEE (Department of Water and Electrical Energy) and in the SIAGAS (System Information Groundwater). The results showed that the largest number of drilling wells, in the municipality, was destined to the domestic and public supply.